2017
DOI: 10.20858/tp.2016.11.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Railways Bolster-Beam Under Commercial Operation Conditions: Over-Traction Andover-Braking

Abstract: Summary.The conditions for the operation of railway systems are closely related to the increase of the commercial demand; as a consequence, the performance of the structural elements of railways changes. The present paper focuses on a study of the structural behaviour of bolster-beams under commercial operation conditions of railway systems, specifically in the dynamic conditions generated in events of over-traction and over-braking on the vehicle running. The proposed work is constructed based on the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the question of meshes matching in the contact area often not considered. For example, the authors of the paper [6] to create of a FE meshes of bogie frame used elements of different types. However, issues related to the coordination of this mesh with other parts not considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, the question of meshes matching in the contact area often not considered. For example, the authors of the paper [6] to create of a FE meshes of bogie frame used elements of different types. However, issues related to the coordination of this mesh with other parts not considered.…”
Section: Introductionmentioning
confidence: 99%
“…1. Its is designed to support the bogie yaw, but maintaining enough comfort for passengers [19]. Several authors reported occurrence of cracks after few years of operation [1,29], reappearing after welding them, so requiring posterior analysis of their causes.…”
Section: Introductionmentioning
confidence: 99%